Evaluation of Properties of Natural Bamboo Fiber for Application in Summer Textiles (Journal of Fiber Bioengineering and Informatics, 2018)
Properties of natural bamboo fibers produced by Neosinocalamus affinis were studied. The natural bamboo fiber was evaluated for its mechanical properties, moisture absorption and thermal properties using Optical Contact Angle Meter (OCA), Thermo-gravimetric Analyzer and Electronic Fiber Strength Tester. Flax and jute fibers were selected as control fibres. The results show that the bamboo fiber is high in tenacity, but low in elongation, similar to all bast fibers. By testing, it was found that the bamboo fiber is low in density with a small contact angle when water dropped, since it is constituted by cellulose along with lignin and hemicellulose. The bamboo fiber has advantages in terms of moisture absorption, drying rate and thermal property. Hence, we predict that the bamboo fiber is suitable for summer textiles, similar to flax and jute fibers.
Keywords: Natural bamboo fiber; mechanical property; moisture absorption; thermo-gravimetric analysis; contact angle; density